2017
DOI: 10.3389/fphys.2017.00612
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Bases of Bicuspid Aortic Valve: The Contribution of Traditional and High-Throughput Sequencing Approaches on Research and Diagnosis

Abstract: Bicuspid aortic valve (BAV) is a common (0.5–2.0% of general population) congenital heart defect with increased prevalence of aortic dilatation and dissection. BAV has an autosomal dominant inheritance with reduced penetrance and variable expressivity. BAV has been described as an isolated trait or associated with syndromic conditions [e.g., Marfan Marfan syndrome or Loeys-Dietz syndrome (MFS, LDS)]. Identification of a syndromic condition in a BAV patient is clinically relevant to personalize aortic surgery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 114 publications
0
45
0
Order By: Relevance
“…Similar to Pz1b morphants, the aortic valves in notch1b mutants are also highly dysmorphic compared to WT controls (Fig.2.C and Movie.S7). The epidermal growth factor receptor (EGFR) gene has also been implicated in the etiology of BAV 17 , furthermore previous research in zebrafish has indicated that chemical inhibition of EGFR using either PKI166 or AG1478 results in defective OFT development 18 . Based on this we treated zebrafish embryos with either inhibitor for 7 days and again assessed aortic valve development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Pz1b morphants, the aortic valves in notch1b mutants are also highly dysmorphic compared to WT controls (Fig.2.C and Movie.S7). The epidermal growth factor receptor (EGFR) gene has also been implicated in the etiology of BAV 17 , furthermore previous research in zebrafish has indicated that chemical inhibition of EGFR using either PKI166 or AG1478 results in defective OFT development 18 . Based on this we treated zebrafish embryos with either inhibitor for 7 days and again assessed aortic valve development.…”
Section: Resultsmentioning
confidence: 99%
“…As with Pz1b morphants and notch1b mutants, inhibition of EGFR results in dysmorphic aortic valves (Fig.2.D,E). Lastly, Endothelial Nitric Oxide Synthase (eNOS) has also been linked to BAV in mice 17 , while treatment of zebrafish embryos with the NOS inhibitor 2-trifluoromethylphenyl imidazole (TRIM) results in defective cardiac development 19 . Therefore, we also treated zebrafish larvae with TRIM and analysed their aortic valves as before and found that TRIM treated larvae also display defective aortic valves (Fig.2.F).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic abnormalities may also belong here, e.g. mutations in NOTCH1, GATA family and ACTA2 genes which lead to BAV formation and could contribute to structural abnormalities of ascending aortic wall [35].…”
Section: Discussionmentioning
confidence: 99%
“…Other likely candidate genes for BAV (12,14,16) AXIN2 Other research associates ZEB2 (OMIM gene 605802) with a complex syndrome manifesting with intellectual disability, facial dysmorphia, speech delay, hydronephrosis, bicuspid aortic valve and absence of corpus callosum (18) and MATR3 (OMIM gene 164015) with bicuspid aortic valve, aortic coarctation and patent ductus arteriosus (19).…”
Section: Syndromic Bav (13-15)mentioning
confidence: 99%